EFEK PEMAPARAN DELTAMETHRIN PADA BROILER TERHADAP AKTIVITAS ENZIM ALANIN AMINOTRANSFERASE, ASPARTAT AMINOTRANSFERASE, GAMBARAN HISTOPATOLOGI HEPAR DAN FEED CONVERTION RATIO - , NEMAY ANGGADEWI NDAONG ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Deltamethrin is a synthetic broad-spectrum insecticide pyretroid, which is used as a organochlorine and organophospat substitute in pest control programs in poultry, cattle, pigs, and dogs, has had a knock-down effect on the target organism and the low bioaccumulation in the environment. Purpose of this study to determine the effects of deltamethrin exposure on the Broilerâs liver histopathological feature, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) enzyme activity, and food conversion ratio (FCR). Fourty DOC Broilers strain New Loghman divided into four group of ten and they were adapted for 5 days prior the treatment. Group I as a control group, group II were given 20 mg/L deltamethrin, group III were given 10 mg/L deltamethrin and exposure deltamethrin concentration 10 mg/L and group IV were given 5 mg/L delthametrin. Deltamethrin was mixed with drinking water and then given to the treatment group for 30 days. Blood samples were taken on day 0, day 15 and day 30 of treatment to determination of ALT and AST enzyme activity. Body weight were recorded once a week for 5 weeks. Feed weighed every day up to 30 days to measure FCR. On day 35, all animal were sacrificed, liver were taken out and fixed in 10% buffer formalin for microscopic examination. Results of the study showed that exposure to 20 mg/L and 10 mg/L deltamethrin for 30 days resulted in the histopathological changes of the liver, such as, fatty degeneration, necrosis and inflammation of the liver. Results of the AST enzyme activity showed that exposure 20 mg/L deltamethrin, but not 10 mg/L and 5 mg/L deltamethrin, for 30 days significantly increased in the activity of AST enzymes (P<0.05) compared to the control group. However, deltamethrin with increasing concentration could not increase the activity of ALT compared with control group (P>0.05). Exposure to 20 mg/L deltamethrin significantly decreased body weight compared to the group given 10 mg /L and 5 mg /L of deltamethrin, with FCR revolves approximately 1.75-1.87. To conclude, deltamethrin within dose of 20 mg/L and 10 mg/L resulted in fatty liver degeneration, necrosis and inflammation. The activity of AST enzymes supported the above histopathological changes. Keywords: pyretroid, deltamethrin, AST, ALT, liver histopathology, broiler